Merancang Aktivitas Pembelajaran untuk Meningkatkan Student Center Learning: Case Study Mata Kuliah Sistem Informasi Manajemen - Asalla, Lydiawati Kosasih (Bina Nusantara University, 2011)
Article talks about student center learning theory related to face-to-face learning at class, how its implementation in the class, and the best practice related to learning activity to increase student center learning. There are some activities that could be done in the process of learning that support student center learning, including group discussion. Advantages in the effective group discussion are the increasing of their understanding towards discussed material and the increasing of social relationship among them. This is assumed to have positive impact to learning process, that is increasing knowledge constructivism and student individual, especially from social behavior. Thus in implementing the effective group discussion is a challenge to lecturers in high numbered student class.